Psychological Impact of COVID-19 Pandemic on Pregnant Mothers – A Survey during the Early Days in Bangladesh - Sharmin Joty, Fahmida; Rahman, Ashrafur (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Objective: The COVID-19 pandemic possess significant risk to public health, including mental health. During pregnancy, women may experience stress and anxiety associated with potential adverse obstetrical outcomes. Stress and anxiety level may also increase during infectious disease outbreaks. Currently, there is no known information on the psychological impact, the effect on individual’s social and/or psychological aspects, and mental health of pregnant women during the COVID-19 pandemic. This study aimed to evaluate the psychological impact of the COVID-19 outbreak on pregnant mothers in Bangladesh in early days. Methods: This was an observational descriptive (survey) study conducted on 60 pregnant mothers during June and July, 2020. The data were collected through online survey form and analysed through SPSS v.20. Results: Mean age of the respondents was 26.7 yrs. Majority of them were from urban community and housewives. Most of the participants were well educated, 65% graduate or above. Twenty three (38.3%) had never visited a doctor during the pandemic period and another 31.7% had visited only once. Twelve mothers faced various pregnancy related complications, but among them three (3/12, 25%) never consulted any medical professional. 38.3% mothers said they faced problem with investigations as there was a fear of contracting the virus during a visit. Majority (78.3%) preferred private hospital to plan their delivery. Most of the mothers (51/60, 85%) said they had not used and/or known about the medications for Covid19, but 50 (83.3%) had bought a PPE. Thirty three (55%) used telemedicine, among them 75% were satisfied. Throughout this pandemic, the pregnant mothers felt depressed (48.3%), restless (31.7%) and undue stress (26.7%). Half the mothers were anxious watching news or any stories on social media about Covid19. Majority 65% did not face any covid related symptoms as they mostly stayed at home. Twenty (33.3%) respondents opined that all pregnant women should be tested for Covid19 regardless of symptoms. Most of the participant recommended telemedicine, availability of good emergency obstetric service and separate transport facility for pregnant mothers. Conclusion: The above results can be used to formulate psychological interventions to improve mental health and psychological resilience of pregnant mothers during the Covid19 pandemic. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(1): 14-19